Safe passage simulation of connected autonomous vehicle platoons at signal-free intersections - Chee, Kenneth Wai Kuin (Nanyang Technological University, 2020)
This project aims to utilise results from numerical simulations of a simplified Connected Autonomous Vehicle (CAV) platoon control model in order to better understand the potential behaviours of CAV platoons at signal-free intersections. The first section will present a modified and simplified version of an existing control model for CAV platoons and how its parameters were determined. The second section will present the results and analysis of numerical simulations, performed on the model in MATLAB, based on six different scenarios: (i) ideal, (ii) with homogeneous communication time delays, (iii) with heterogeneous communication time delays, (iv) with network noise disturbances, (v) with network noise disturbances and homogeneous communication time delays, and (vi) with network noise disturbances and heterogeneous communication time delays. The results indicate that to ensure safe-passage for a CAV platoon across a signal-free intersection, the constant control gains of the simulation model must be appropriately determined.